2019
DOI: 10.3775/jie.98.90
|View full text |Cite
|
Sign up to set email alerts
|

Production Test of Torrefied Woody Biomass Solid Fuel in an Original Small Scale Plant: (2) Effects of Automatic Temperature Control in Torrefaction and the Use of Additives in Pelletization

Abstract: A small-scale demonstration plant, which consists of a rotary kiln-type oven and a ring die-type pelletizer, was manufactured to produce upgraded wood fuel by torrefaction. In this study, we improved the temperature control and the pelletization methods. The oven and pelletization operations were optimized by implementing automatic temperature control of the torrefaction oven, and the use of additives in pelletization; which resulted in improvements in pellet productivity. A commercial scale image of the torre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…At the same time, domestic pellet production was only~140,000 t from~150 domestic pellet mills [13], indicating that the production of local pellet mills in Japan has been operating on a small scale. Recently, the concept of producing torrefied pellets using small-scale production in rural areas has been proposed [14][15][16], in which case the torrefied fuel would require heat use and stable storage. After their fundamental studies on the effects of torrefaction treatment conditions on mass yields, calorific values, and mechanical durability at a laboratory scale [17][18][19], Yoshida et al [16,20,21] constructed a demonstration plant aiming at small-scale use, using a treatment amount of 20 kg/h to continuously produce torrefaction chips from raw wood chips.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, domestic pellet production was only~140,000 t from~150 domestic pellet mills [13], indicating that the production of local pellet mills in Japan has been operating on a small scale. Recently, the concept of producing torrefied pellets using small-scale production in rural areas has been proposed [14][15][16], in which case the torrefied fuel would require heat use and stable storage. After their fundamental studies on the effects of torrefaction treatment conditions on mass yields, calorific values, and mechanical durability at a laboratory scale [17][18][19], Yoshida et al [16,20,21] constructed a demonstration plant aiming at small-scale use, using a treatment amount of 20 kg/h to continuously produce torrefaction chips from raw wood chips.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the concept of producing torrefied pellets using small-scale production in rural areas has been proposed [14][15][16], in which case the torrefied fuel would require heat use and stable storage. After their fundamental studies on the effects of torrefaction treatment conditions on mass yields, calorific values, and mechanical durability at a laboratory scale [17][18][19], Yoshida et al [16,20,21] constructed a demonstration plant aiming at small-scale use, using a treatment amount of 20 kg/h to continuously produce torrefaction chips from raw wood chips. Burning trials of the torrefied pellets produced in this demonstration plant for a commercial pellet stove revealed that the torrefied pellets exhibited a faster ignition time than normal pellets [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of burning trials for the torrefied pellets in a commercial pellet stove, we found that the torrefied pellets demonstrated faster ignition time than normal pellets. We thus designed a commercial-scale plant to produce torrefied wood pellets at a small scale (3,000 t of torrefied fuel per year) using local wood resources [9]. However, as pointed out in the report, these pellets should have a higher cost than normal wood pellets in production [2,4,9].…”
Section: Introductionmentioning
confidence: 99%
“…We thus designed a commercial-scale plant to produce torrefied wood pellets at a small scale (3,000 t of torrefied fuel per year) using local wood resources [9]. However, as pointed out in the report, these pellets should have a higher cost than normal wood pellets in production [2,4,9]. Production at a large scale, such as for coal co-firing power, achieves cost-effectiveness by including transportation to a power station and subsequent preparation prior to combustion.…”
Section: Introductionmentioning
confidence: 99%